Leprosy in Pre-Columbian Peru - Pesce, Hugo (1955)
The main sources of knowledge that can be invoked to resolve the existence of leprosy in the pre-Columbian era are, in relation to Peru, the following: - Relics of pre-Columbian civilizations. - Tales of the chroniclers. - Philological studies. - Previous existence of certain diseases of regional type. Also worth bearing in mind similar sources and facts about other countries in America.